2009
DOI: 10.1093/toxsci/kfp057
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled and Multi-Walled Carbon Nanotubes Promote Allergic Immune Responses in Mice

Abstract: The adjuvant effect of particles on allergic immune responses has been shown to increase with decreasing particle size and increasing particle surface area. Like ultrafine particles, carbon nanotubes (CNTs) have nano-sized dimensions and a large relative surface area and might thus increase allergic responses. Therefore, we examined whether single-walled (sw) and multi-walled (mw) CNTs have the capacity to promote allergic responses in mice, first in an sc injection model and thereafter in an intranasal model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
153
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(168 citation statements)
references
References 37 publications
8
153
4
1
Order By: Relevance
“…The study recognized the SW-CNTs as a respiratory toxicant, responsible for neurotoxicity and cell cycle defects. MW-CNTs are also known for increased micronuclei frequency and chromosomal aberrations, promotion of allergic response in mice, activation of cyclooxygenase enzymes through suppression of systemic immune function in spleen and altered gene expression in the liver [173][174][175][176][177]. Other effects of MW-CNTs include apoptosis, phenotypic defects, toxicity in bacteria and formation of abnormal spinal cords in zebrafish embryo [178][179][180].…”
Section: Effects On Organ Systemsmentioning
confidence: 99%
“…The study recognized the SW-CNTs as a respiratory toxicant, responsible for neurotoxicity and cell cycle defects. MW-CNTs are also known for increased micronuclei frequency and chromosomal aberrations, promotion of allergic response in mice, activation of cyclooxygenase enzymes through suppression of systemic immune function in spleen and altered gene expression in the liver [173][174][175][176][177]. Other effects of MW-CNTs include apoptosis, phenotypic defects, toxicity in bacteria and formation of abnormal spinal cords in zebrafish embryo [178][179][180].…”
Section: Effects On Organ Systemsmentioning
confidence: 99%
“…The protein corona can also stimulate opsonisation by macrophages in vivo, thereby activating the complement system and evoking an immune reaction 70 . Another plausible pathway to immunotoxicity is the enhancement of an allergic immune response, which by Nygaard et al observed for single-and multi-walled carbonnotubes (CNT) in mice 71,72 .…”
Section: Common Mechanisms Causing Nanotoxicitymentioning
confidence: 99%
“…44 Then the entire process of reconstitution occurs, from the successful interaction between cells and cells and ECM, avoiding initiation of an immune response. 45 One of the most popular materials used in scaffolds for tissue engineering was discovered in 1991 and revolutionized the research field: CNTs. 17 These nanotubes, since they started being studied, have demonstrated a huge number of interesting characteristics; for example, they have remarkable electrical and mechanical properties and chemical stability.…”
Section: Required Characteristics For a Desirable Scaffold And Its Immentioning
confidence: 99%
“…50 Nygaard and collaborators demonstrated that in mice, the adjuvant effect of particles on allergic immune responses increases with decreasing particle size and increasing particle surface area, and that CNTs promote allergic responses in mice. 45 In this way, researchers face the challenge of modifying CNT surface to avoid evoking immune responses and to promote successful regeneration as part of a scaffold.…”
Section: Required Characteristics For a Desirable Scaffold And Its Immentioning
confidence: 99%